Effectiveness of kettle bell workout on abdominal muscles strength In recreational athletes: a randomized controlled trial - Ismat Ullah; Amna; Natasha Amjad; Naseer Ullah; Danish Rauf; Liao Qin (The Rehabilitation Journal)
Background: Recreational athletes often lack access to specialized strength training as kettlebell workouts on abdominal muscle strength can provide valuable insights